2002
DOI: 10.1889/1.1827846
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature poly‐Si TFT transferred onto plastic substrates by using surface free technology by laser ablation/annealing (SUFTLA®)

Abstract: Abstract— A novel technology that makes it possible to transfer electronic devices from an original substrate to another substrate is introduced. Because laser irradiation is utilized during the transfer process, this technology was named SUFTLA® (surface free technology by laser ablation/annealing). Low‐temperature poly‐Si TFTs first manufactured on a quartz substrate were transferred onto a PES substrate without any damage or characteristic degradation. A trial TFT‐LCD device with peripheral integrated drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…6 Moreover, it is also possible to fabricate them on many types of the plastic substrates by using device transfer such as Suftla 10 without drastic modifications of the above-mentioned fabrication process. 7,8 The measurement system is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Moreover, it is also possible to fabricate them on many types of the plastic substrates by using device transfer such as Suftla 10 without drastic modifications of the above-mentioned fabrication process. 7,8 The measurement system is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…This artificial retina is expected to be suitable for human beings because it can potentially be fabricated on flexible, harmless, plastic and organic substrate. [6][7][8]…”
Section: Introductionmentioning
confidence: 99%
“…While the authors of the previous papers [2]- [4] demonstrated relatively small flexible TFT LCDs (1-3 in) using the transfer technology, they did not mention the utilization of the technology to larger substrates. From the standpoint of mass production, high rates and satisfactory uniformity over large substrate areas are required for the glass etching.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the TFT flexible substrates, transfer processes have been developed [1]- [3], in which low-temperature poly-Si (LTPS) TFT arrays were fabricated on a glass substrate using ordinary processing and then transferred onto a plastic substrate. One of these transfer processes included applying a protective film on the TFT array surface and etching the glass substrate away using hydrofluoric (HF) acid [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some adhesives have been used in the transfer processes [1]- [3], which could cause degradation of the TFT performances due to adhesive contamination. It is, therefore, necessary to develop a transfer process free of contamination, while attaining a high rate of glass etching.…”
Section: Introductionmentioning
confidence: 99%